Integrated, Accountable Care For Medicaid Expansion Enrollees: A Comparative Evaluation of Hennepin Health. (February 2020) - Vickery, Katherine D.; Shippee, Nathan D.; Menk, Jeremiah; Owen, Ross; Vock, David M.; Bodurtha, Peter; Soderlund, Dana; Hayward, Rodney A.; Davis, Matthew M.; Connett, John; Linzer, Mark
Hennepin Health, a Medicaid accountable care organization, began serving early expansion enrollees (very low-income childless adults) in 2012. It uses an integrated care model to address social and behavioral needs. We compared health care utilization in Hennepin Health with other Medicaid managed care in the same area from 2012 to 2014, controlling for demographics, chronic conditions, and enrollment patterns. Homelessness and substance use were higher in Hennepin Health. Overall adjusted results showed Hennepin Health had 52% more emergency department visits and 11% more primary care visits than comparators. Over time, modeling a 6-month exposure to Hennepin Health, emergency department and primary care visits decreased and dental visits increased; hospitalizations decreased nonsignificantly but increased among comparators. Subgroup analysis of high utilizers showed lower hospitalizations in Hennepin Health. Integrated, accountable care under Medicaid expansion showed some desirable trends and subgroup benefits, but overall did not reduce acute health care utilization versus other managed care.